ІМПЛІЦИТНІСТЬ АНГЛОМОВНОЇ ВЕРБАЛЬНОЇ ПОВЕДІНКИ - Гладуш, Н.Ф. (Studia Philologica, 2014)
The article analyzes relevant features of Modern English Speech Behavior. A special attention is given to such relevant features of English verbal behaviour as implicit and indirect, non categorical and compromising nature of English Speech communication. In conclusions, an attempt is made to summarize these idiomatic features and their relevance for teaching English.